Sexual and Reproductive Health Information and Services in Public Libraries: A National Survey of Public Library Professionals - Alvarez, Barbara A. (Public library quarterly (New York, N.Y.), 2024)
This paper presents the major findings from a nationwide survey about sexual and reproductive health information services in public libraries. The survey was conducted between March 3 and May 1, 2022 through an online survey. The participants were library professionals who work in public libraries. This analysis reviews data from 179 respondents from 12 states. Most survey participants believe that their library needs to increase sexual and reproductive health information services. However, findings from the survey reveal the complicated nature of providing this information, including intellectual freedom and self-censorship issues.